The evolution of human population distance to water in the USA from 1790 to 2010 - Yu Fang (Nature Portfolio, 2019)
There are dynamic and complex interactions between population and water resources. Here the authors studied the spatio-temporal relationship between human and water resources in conterminous US and found that dynamic human distance to water reflects the changing societal reliance on adjacency to major rivers.